TINJAUAN FIQH SIYASAH DUSTURIYAH TERHADAP UNDANG-UNDANG NOMOR 16 TAHUN 2011 TENTANG BANTUAN HUKUM - Utari Lorensi Putri; Sulastri Caniago (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
The focus of the study in this research is on the perspective of fiqh siyasah dusturiyah to the Legislation Number 16 of 2011 concerning Legal Aid. The purpose of this paper is to explain and analyze how the implementation of Legal Aid towards the fulfillment of the rights and justice of the people based on the Indonesian constitution and fiqh siyasah dusturiyah perspective. Legal Aid itself is so that the rights of the people can be fulfilled in cases in court and out of court. In carrying out Legal Aid must use the principle of justice. Justice is meant to place the rights and obligations of everyone in a proportional, proper, correct, good and orderly manner, the principle of equality in law is that everyone has the same rights and treatment before the law and the obligation to uphold the law. In Islamic courts, the idea of providing legal aid has been formed. The principles of justice and equality before the law or the fulfillment of people's rights are included in the concept of legal aid. The provisions of Islamic law are the most fundamental basis for the existence of Legal Aid in the Islamic legal process.